The Impact of Orphanage Homes on the Personality Development of Primary School Students in Nigeria - Magdalene Ifeoma Ogbemudia; Esther Chinedu Wordu; Victor Mafone Alasa; Nwajiaku Esther Okwudili (Gagasan Pendidikan Indonesia, 2022)
This study investigated the impact of orphanage home on the personality development of students, using the Akwa Ibom State, South Nigeria as the research context. Three variables were considered in this study which includes impact of self-image on personality development, impact of self-worth on personality development and impact of physical well-being on personality development.  A sample size of seventy-five (75) students participated in the study that has the descriptive design as research design. The instrument use for data collection was orphanage Home and Pupils’ Personality Development Questionnaire (OHPPDQ). The data set generated from the participants was analyzed with the independent t-test statistics and the result obtained from the study at 0.5 level of significant showed that self-image, self-worth and physical well-being of students significantly influence the personality development of Orphanage student in this part of the country, and the necessary recommendations were made.